The Influence of Diagenesis Processes on the Reservoir Properties of Hartha Formation in Selected oil Fields, Northern Iraq - Nooralddin, Amel K.; Al-hadidy, Aboosh H.; Nasser, Medhat E. (Iraqi Journal of Science, 2022)
The Hartha Formation reservoir was evaluated to be produced in the near future in Y oil and J fields, West of the Tigris River in northern Iraq. Due to geological data analysis of the Hartha facies and diagenesis could enhance oil production with minimized risks, this research tried to deal with data to support the oil production. The Hartha reservoir is subdivided into five-rock units, Har-1, 2, 3, 4 and 5. It is of Heterogenic facies limestone, dolomite, dolomitic limestone and argillaceous dolomite. The Hartha Formation is a clean carbonate; it has an effective porosity. It consists of lime mudstone-packstone skeletal grain. This conclusion is based on the lithology, core microfacies, cutting, thin section and log interpretation variability.  The study aims to characterize the depositional and diagenetic properties of the Hartha carbonate and their effects on the reservoir quality. This research indicated that the depositional setting is a gentle slope ramp including outer, mid and inner ramps. The dissolution and dolomitization in near-surface and marine environments formed secondary porosity types as a vuggy, cavern, and melodic. The fracture is a good reservoir in the upper part of the Hartha reservoir. The lower section is affected by other diagenetic processes  causing a destructive effect on porosity such as compaction, Neomorphism  and cementation. The measured and calculated porosity with an integration of the measured permeability in the Hartha Reservoir gave a good reservoir quality to the formation. These data are coming from the analysis of the primary and secondary porosity. The petrophysical cut-off provided an excellent result for the rock properties as the net to gross ratio of the most units of the Hartha Reservoir.